Arranjos produtivos locais e desenvolvimento: uma análise do setor têxtil-vestuário no Estado do Rio de Janeiro - Nascimento, Ricardo Brito do (2006)
The present work aims at to investigate the importance of the local productive arrangements of the textile and clothing sector to conceive employment generation, productive units and average remuneration to the towns of Petrópolis, Nova Friburgo and Cabo Frio, all of them located in the State of Rio de Janeiro, from the period of 1995 to 2004. The hypothesis that guides this work is that the local productive arrangements contribute for the growth and local development of form to increase the employment and the income and to reduce the local poverty. For this purpose, it was used the data from RAIS/MTE. The decision of studying textile and clothing sector is due to this sector is important to State of Rio de Janeiro, regarding the creation of employment. In spite of the crisis that it went though, the sector during the commercial opening of the decade of 1990, it still has important representation nowadays in the creation of employments, for the state transformation industry. For the research of local productive arrangements, that highlights the importance of the geographic proximity among the small and medium size companies to overcome the common production difficulties by the interaction and cooperation, it will be used, in the first chapter, the analyticteorical statement that deal with the evolutionist approach about the national and local system of innovation. The second one will contain the characterization of the local productive arrangements of the towns by means of employment relative data, establishment and remuneration and of recent research that has identified the interactions among the agents of the arrangements. The third one will compare the regions that are in the arrangements to bigger regions as the micro region, the state and the country; to identify possible productive gargles in the chain of the arrangements; to investigate the existence of arrangements impacts upon other sectors in the towns and the expansion of the activities of the arrangements for the close regions to the towns and to verify the evolution of the remuneration in the arrangements during the period in question. The last one will present the conclusions of the work.